Flow and heat transfer at a general three-dimensional stagnation point in a nanofluid - Bachok @ Lati, Norfifah; Mohd Ishak, Anuar; Mohd Nazar, Roslinda; Pop, Ioan (Elsevier, 2010)
The problem dealing with steady three-dimensional stagnation point flow in a nanofluid is investigated. By using appropriate transformation for velocity and temperature, the basic equations governing the flow and heat transfer are reduced to a set of ordinary differential equations. These equations subjected to the associated boundary conditions are then solved numerically. The effects of the nanoparticle volume fraction φ and the ratio of the gradient of velocities c on the flow and heat transfer characteristics are thoroughly examined.